Why kill the innocent : a Sebastian St. Cyr Mystery - Harris, C. S.; Moore, Christina; Recorded Books, Inc. (Prince Frederick, Md. : Recorded Books, 2018)
In the newest mystery from the national bestselling author of Where the Dead Lie, a brutal murder draws Sebastian St. Cyr into the web of the royal court, where intrigue abounds and betrayal awaits. London, 1814. As a cruel winter holds the city in its icy grip, the bloody body of a beautiful young musician is found half-buried in a snowdrift. Jane Ambrose's ties to Princess Charlotte, the only child of the Prince Regent and heir presumptive to the throne, panic the palace, which moves quickly to shut down any investigation into the death of the talented pianist. But Sebastian St. Cyr, Viscount Devlin, and his wife Hero refuse to allow Jane's murderer to escape justice. Untangling the secrets of Jane's world leads Sebastian into a maze of dangerous treachery where each player has his or her own unsavory agenda and no one can be trusted. As the Thames freezes over and the people of London pour onto the ice for a Frost Fair, Sebastian and Hero find their investigation circling back to the palace and building to a chilling crescendo of deceit and death ...
In container (17 cm).
Title from container.
Compact disc.
Narrated by Christina Moore.
Keywords: Saint Cyr, Sebastian -- (Fictitious character) -- Fiction; Great Britain -- History -- George III, 1760-1820 -- Fiction; Mystery fiction; Audiobooks